Flavonols reduce aortic atherosclerosis lesion area in apolipoprotein E deficient mice: A systematic review and meta-analysis. - James Phie; Smriti M Krishna; Joseph V Moxon; Safraz M Omer; Robert Kinobe; Jonathan Golledge; Jonathan Golledge (PLoS ONE)
Diets rich in flavonoids have been reported to have beneficial effects in the primary prevention of cardiovascular events. There are limited data, however, on the cardiovascular benefits of purified flavonoids. The aim of this systematic review and meta-analysis was to examine the reported effects of isolated flavonoids on aortic atherosclerosis in a mouse model. Medline, Pubmed, Science direct and Web of Science were searched to identify studies which examined the effect of isolated flavonoids on aortic atherosclerosis in apolipoprotein E deficient mice. A meta-analysis was performed to determine the overall effect of the flavonoids, and sub-analyses were performed to compare the effects of the flavonols and flavan-3-ols. Eleven studies, which examined a total of 208 mice receiving a flavonoid and 126 control mice, were included. Overall the flavonoids significantly reduced aortic atherosclerosis (SMD 1.10, 95% CI 0.69, 1.51). Of the 18 flavonoid interventions examined 12 were flavonols and 3 were flavan-3-ols. Sub-analyses suggested that the flavonols (SMD 1.31, 95% CI 0.66, 1.91) but not the flavan-3-ols (SMD 0.33, 95% CI -0.19, 0.85) significantly decreased atherosclerosis area. Of the eleven studies, only one examined histological markers of atherosclerosis plaque stability. Most studies did not report blinding of outcome assessors or reproducibility of the primary outcome, and did not justify the sample size used and flavonoid dose administered. Based on the included studies, the flavonols appear to be the most effective flavonoids for reducing aortic atherosclerotic lesion area in apolipoprotein E deficient mice.